PENGGUNAAN MEDIA PEMBELAJARAN IPA TERPADU BERBASIS KOMPUTER DENGAN MACROMEDIA FLASH 8 PADA POKOK BAHASAN UNSUR, SENYAWA DAN CAMPURAN TERHADAP KEJELASAN, KEDALAMAN DAN KETEPATAN ISI MATERI - Wina Mariana Parinduri (Jurnal Sintaksis, 2019)
Macromedia flash has a lot of advantages compared with other animation software. For instance, the program is object-oriented, which can design based on the vector that used as a software to create Websites and other advantages. The students who use the computer program may accomplish the lesson about 13, 75 hours. On the other side, the students use direct lesson need 24 hours. Besides, more than 560 in the senior high school use the computer program “ EnviroQuest” and ROD-CD. The result of ROD-CD is shown 93% of the students find their aim after learning its program. 70 % of students state that they get a lot of knowledge, and 97% of students say that they love its computer program. In short, the advantage of using the computer program as a learning media has a lot of benefits. This research has already conducted in chemistry laboratory FMIPA UNIMED, and the media has examined in MTS Negeri 3 Medan on Mei 2010. The instrument used in this research is the usage of the questionnaire to reveal the students’ responses toward the learning media based on computer media namely: Macromedia flash 8. In conclusion, the result of this research is the media has given the material clearly, and the content of the material is more clearly.